A Technical Report: Geotechnical & Geophysical Properties Study of Soil about Tabeen-Dokan in Sulamania Region - Mohamad, Ahmed Salih (Sulaimani Journal for Pure and Applied Sciences, 2007)
This research including field and laboratory detailed investigation for study of physical and chemical engineering of Tabeen-Dokan in Sulymania Region. Experimental work included two main aspects, that was taken disturbed and undisturbed soil samples carry out to several tests in laboratory of soil mechanic. The second part was related to the field tests for calculating geophysical properties of soil in addition defining of water table level . The results of analysis collection data indicate that the soil in this region have a good bearing capacity but have some problem in swelling index and the water table was not observed during the investigation period.
Keywords: Augers; laboratory soil test; soil investigation; and swelling